Flood Analysis of Pepe Baru River Sub-Watershed Using HEC-RAS 4.1 Aplikasi - Wijayanti, Paska; Sungkono, Kukuh Kurniawan Dwi; Arbianto, Reki; Utomo, Dhody Budi (Journal of Civil Engineering and Planning (JCEP), 2025)
The conversion of catchment areas into built-up land has increased surface runoff and reduced natural river storage capacity, thereby elevating flood risk, particularly during high rainfall events. One area that frequently experiences flooding is Sekip Kadipiro, located within the Pepe Baru Sub-watershed of the Pepe Watershed system in Surakarta City. The hydrological connection of this area to the Pepe Watershed makes it highly vulnerable to flooding. In January 2023, heavy rainfall caused inundation affecting approximately six residential houses in Sekip Kadipiro. This study aimed to determine the 20-year return period design flood discharge and to simulate flooding in the Sekip Kadipiro area using the HEC-RAS 4.1 application. The analysis utilized 17 years of rainfall data, physical characteristics of the Pepe Baru Sub-watershed, and river geometry data processed using QGIS 3.10. The 20-year design rainfall was calculated using the Log Pearson Type III method, resulting in a value of 359.422 mm. Hourly rainfall distribution was analyzed using the ABM method for a duration of four hours, while effective rainfall was determined using the SCS-CN method. The design flood discharge for the 20-year return period was estimated using the Nakayasu Synthetic Unit Hydrograph method, yielding a peak discharge of 1745.42 m³/s. Hydraulic simulation results from HEC-RAS 4.1 indicate that floodwater levels reach an average of 1.75 m above the embankment crest. This demonstrates that the existing river channel capacity is insufficient to convey the design flood discharge, resulting in overflow and a high potential for flooding in surrounding residential areas.